Flow.co / Muhammad Akram Hafeez Hj Mahusain, Muhammad Amirui Hafiz Rosman … [et al.] - Hj Mahusain, Muhammad Akram Hafeez; Rosman, Muhammad Amirui Hafiz; Massna Sudarmaji, Mas Izzati; Hishamudin, Nurul Syazwina; Nooridzahir, Noor Syahirah (2019)
Flow.Co offer shawl is a new shop that will be opening in Bangi, Selangor, to sell women's hijabs, women shawl that have zip and button in variety of style, color, size and design. The idea of creating the business's name came from the team where Flow means that our shawl very flowing went use and the symbol of zip and button represent that our shawl will have zip or button to extend the shawl and it more easy to use. So zip and button concept that we use is our trademark of our shawl.